DECISION SUPPORT SYSTEM FOR DETERMINING LEVELS OF CRUDE PALM OIL USING FUZZY MADM (MULTIPLE ATTRIBUTE DECISION MAKING) USING THE SAW (SIMPLE ADDTIVE WEIGHTING) METHOD - Furqan, Mhd; Nasution, Yusuf Ramadhan; Irsyad, Fauzan (ZERO: Jurnal Sains, Matematika dan Terapan, 2022)
PT.UKINDO BLANKHAN – POM is one of many large oil palm plantations that produces crude palm oil. The quality requirements for palm oil used as a raw material in the food industry and the non-food industry are distinct. Consequently, authenticity, purity, freshness, and other aspects need to be given more thought. The crude palm oil content is still selected manually in the processing section. It is challenging to process this, and it does not completely rule out the possibility of assessment errors. Based on the assessment above, determining high-quality oil frequently presents challenges, particularly when it comes to valuing crude oil levels or aspects in accordance with quality and standards. In light of these issues, a system that can assist in determining the level and quality of raw oil is required. Consequently, developing a method for determining the content of crude palm oil using Fuzzy MultiAttributeDecision Making and Simple Additive Weighting methods. The Fuzzy MultiAttribute Decision Making methodiisiused toifind alternativesifrom a number of alternativesiwith predeterminedicriteria. Whileithe Simple Additive Weighting methodiis usedito rank theiexisting alternatives. Theiresults ofithis studylcan belused asla tooliin makingldecisions tolget a good oil content.